Pengaruh Green Accounting, Corporate Social Responsibility Terhadap Financial Performance - Viga Ardhinata; Dirvi Surya Abbas; Basuki Basuki (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The purpose of this study is to determine the effect of green accounting, corporate social responsibility, on financial performance. The population of this study is Basic Industrial and Chemical Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2016-2022 Period. This study used a quantitative approach. The population in this study is 15 basic industrial and chemical sector companies listed on the Indonesia Stock Exchange. The sampling technique used is Purposive Sampling. The type of data used in this study is secondary data. Based on the result it show that green accounting has a negative effect on financial performance. Corporate social responsibility have a significant positive effect on financial performance.